Traditions and Unique Characteristics of Folk Dance among Ethnic Minorities in Khulunbuir - Guo Sarula (Mongolian Journal of Arts and Culture, 2025)
Hulunbuir City, located in the Inner Mongolia Autonomous Region (IMAR) of the People’s Republic of China, is home to several ethnic minorities, including the Mongols, Daur, Orchon, and Evenki. Each of these groups possesses its own distinct characteristics and rich cultural heritage. In this article, we focus on the Daur and Orchon peoples, who are among the least studied ethnic groups in Hulun buir. Although they share similar geographic and weather conditions, their lifestyles, faith and beliefs, and traditions different significantly. As a result, their folk dances exhibit unique movements and accompanying melodies. Based on our field research, we aim to highlight the distinctive features of their dance traditions and the cultural expressions embedded within them. Хөлөнбуйрын цөөн тоот үндэстний ардын бүжгийн уламжлал, өвөрмөц онцлог Хураангуй: БНХАУ-ын ӨМӨЗО-ны Хөлөнбуйр хот нь монгол, дагуур, орчоон, эвенк зэрэг цөөн тоот үндэстнээс бүрдэх бөгөөд үндэстэн бүр өөр өөрийн өвөрмөц онцлогтой, ахуй соёлын арвин баялаг өв соёлыг хадгалан тээгч билээ. Бид энэ өгүүлэлдээ Хөлөнбуйрын цөөн тоот үндэстний дотроос хамгийн бага судлагдсан дагуур, орчоон үндэстэн нь оршин амьдрах газар нутаг, байгаль цаг уурын хувьд ижил боловч аж төрөх хэлбэр, шашин шүтлэг, ёс уламжлал өөр ард түмэн тул өөр өөрийн гэсэн өвөрмөц онцлог бүхий бүжгийн хөдөлгөөн, түүнээ илтгэх ая дуутай байдгийг өөрсдийн биеэр явж судалсан хээрийн шинжилгээний дүндээ тулгуурлан гаргахыг хичээсэн болно. Түлхүүр үгс: Хөлөнбуйрын цөөн тоот үндэстэн, дагуур, орчоон, эвенк, ардын бүжиг, уламжлал, онцлог